Homicide in hardcover : a bibliophile mystery - Carlisle, Kate (New York : Obsidian Mystery, 2009)
When she finds her mentor lying in a pool of blood, clutching a priceless and supposedly cursed copy of Goethe's Faust, book restorer Brooklyn Wainwright is accused of murder and theft by an annoyingly attractive British security officer.
Keywords: Books -- Conservation and restoration -- Fiction; Murder -- Investigation -- California -- San Francisco -- Fiction; Detective and mystery fiction